2020
DOI: 10.1038/s41598-020-77841-1
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal factors and risk of seropositive rheumatoid arthritis in postmenopausal women: a nationwide cohort study of 1.36 million women

Abstract: In previous literature regarding development of rheumatoid arthritis (RA), female reproductive factors have been described as protective factors, risk factors, or irrelevant, leading to inconsistent results. The aim of this study was to investigate the effect of female reproductive factors on the incidence of seropositive RA. A large population-based retrospective cohort of the National Health Insurance Service data in South Korea was used. Postmenopausal women who participated in both cardiovascular and breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 51 publications
(121 reference statements)
1
13
0
1
Order By: Relevance
“…Several earlier studies have demonstrated EM as a risk factor for the development of RA 8 14. Conversely, recent large-scale cohort studies have shown either no association or a significant association between age at menopause and RA risk only among smokers 17 18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several earlier studies have demonstrated EM as a risk factor for the development of RA 8 14. Conversely, recent large-scale cohort studies have shown either no association or a significant association between age at menopause and RA risk only among smokers 17 18…”
Section: Introductionmentioning
confidence: 99%
“… 8 14 Conversely, recent large-scale cohort studies have shown either no association or a significant association between age at menopause and RA risk only among smokers. 17 18 …”
Section: Introductionmentioning
confidence: 99%
“… Diagnostic code Prescription ICD-10 Registration V code ATC code or ingredients Days or no. of prescription Autoimmune diseases Rheumatic Systemic lupus erythematosus 41 M32 V136 Dermatomyositis/ polymyositis 42 M33 V137 Systemic sclerosis 43 M34 V138 Sjogren’s syndrome 44 M350 V139 Ankylosing spondylitis 45 M45 V140 Rheumatoid arthritis 46 M05 V223 Non-rheumatic Type 1 DM E10 A10 (drugs used in diabetes) ≥ 1 year Grave’s disease 47 E050, E058, E059 Methimazole, propylthiouracil, or carbimazole ≥ 60 days Hashimoto’s thyroiditis 47 E063, E069 Levothyroxine sodium or liothyronine sodium ≥ 60 days Crohn’s disease 48 …”
Section: Introductionmentioning
confidence: 99%
“…From 2008 to 2019, the participation rate in health check-ups was 67.3-75.6% in the total population, 63.7-89.5% in people ages 20-29 years, and 72.2-85.2% in people ages 30-39 years (25). Health check-up information is collected by the NHIS and is used in various epidemiologic studies, such as studies identifying risk factors for disease, in connection with other information in the claims database (16,26,27).…”
Section: Methodsmentioning
confidence: 99%